Metal material surface treatment method and new application of treatment liquid
By using a nitric acid-containing treatment solution to immerse the nickel-titanium alloy and stainless steel, an oxide film is formed, which solves the problem of easy damage to the surface oxide layer and significantly improves the corrosion resistance and service life of the material.
Patent Information
- Application Number
- CN202310763688.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2024-12-27
AI Technical Summary
Ni-titanium alloys and stainless steels are susceptible to body fluid corrosion in medical applications, resulting in damage to the surface oxide layer, reducing corrosion resistance, and affecting material stability and service life.
The metal material is soaked with a treatment solution containing 5% to 15% nitric acid and 85% to 95% water to form an oxide film, and the integrity and stability of the film are ensured through the cleaning and drying steps.
It significantly improves the breakdown voltage of metal materials, enhances corrosion resistance, and extends service life, especially in difficult parts of nickel-titanium alloys and stainless steel, which effectively avoids the problem of incomplete oxide films.
Smart Images

Figure BDA0004305505100000091 
Figure BDA0004305505100000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of surface protection treatment, and in particular to a method for treating the surface of a metal material and a use of a treatment solution containing nitric acid and water in treating the surface of a metal material. Background Art
[0002] Nickel Titanium Alloy, also known as NiTi alloy or shape memory alloy, is a metal alloy with shape and super elasticity, composed of nickel and titanium. This alloy can maintain a certain shape at low temperatures, but will return to its original shape when heated or subjected to force. The shape memory and super elasticity of nickel-titanium alloy make it widely used in medicine, aerospace, automobile, electronics and other fields. In the medical field, nickel-titanium alloy is mainly used to manufacture various medical devices and equipment, such as: braces, nickel-titanium alloy is one of the common materials for manufacturing braces, its shape memory and superelasticity enable it to automatically adjust its shape in the human mouth and apply appropriate force for correction; vascular stents, nickel-titanium alloy is also widely used to manufacture vascular stents, when the stent is implanted into a damaged blood vessel, it can automatically adjust its shape to adapt to the shape of the blood vessel and keep the blood vessel patency; endoscopes, nickel-titanium alloy can be made into very thin tubular structures, suitable for preparing endoscopes for respiratory and digestive tract examinations; artificial joints and bone stents, nickel-titanium alloy has good biocompatibility and mechanical strength, so it is widely used in the manufacture of artificial joints and bone stents, pacemakers and neural electrical stimulators. In addition, stainless steel is also a commonly used metal material for various medical devices and equipment. Medical devices and equipment may be exposed to corrosive environments such as human body fluids and blood during use, and the surface may be corroded by corrosive substances, forming rust or pollution, resulting in a decrease in material performance, and even causing serious consequences such as inflammation or infection. Summary of the invention
[0003] Nickel-titanium alloy and / or stainless steel need to go through a polishing process and various subsequent treatments before they can be made into various medical devices and equipment. Polishing can improve the corrosion resistance of the metal material surface to a certain extent, make the sample surface highly bright, and attach a layer of fine titanium dioxide film to improve the stability and uniformity of the alloy. However, the oxide film formed on the surface is relatively thin, and various subsequent treatments can easily damage the surface of the metal material, resulting in a serious reduction in the corrosion resistance of the metal material. In response to the above problems, the present application provides a simple and convenient method for surface treatment of metal materials, by immersing the metal material in a treatment solution containing nitric acid and water, so that an oxide film is formed on the surface of the metal material, which can not only effectively improve the damage of the oxide layer on the surface of the metal material by external force, but also maximize the breakdown voltage of the metal material, thereby improving the corrosion resistance of the metal material.
[0004] The specific technical solutions of this application are as follows:
[0005] 1. A method for surface treatment of a metal material, wherein the method comprises the following steps:
[0006] The metal material is immersed in the treatment liquid to form an oxide film on the surface of the metal material;
[0007] The treatment liquid comprises nitric acid and water. In the treatment liquid, the volume fraction of nitric acid is 5% to 15%, and the volume fraction of water is 85% to 95%.
[0008] 2. The method according to item 1, wherein the soaking treatment time is 1 to 5 hours, preferably 2 to 3 hours.
[0009] 3. The method according to item 1, wherein the volume fraction of nitric acid in the treatment liquid is 8% to 12%, and the volume fraction of water is 88% to 92%.
[0010] 4. The method according to any one of items 1 to 3, wherein the treatment liquid consists of nitric acid and water.
[0011] 5. The method according to any one of items 1 to 4, wherein after the oxide film is formed on the surface of the metal material, the method further comprises the steps of cleaning and drying the metal material.
[0012] 6. The method according to any one of items 1 to 5, wherein the metal material is nickel-titanium alloy and / or stainless steel.
[0013] 7. Use of a treatment liquid containing nitric acid and water in the surface treatment of metal materials, wherein the volume fraction of nitric acid in the treatment liquid is 5% to 15%, and the volume fraction of water is 85% to 95%.
[0014] 8. The use according to item 7, wherein the surface treatment of the metal material comprises the following steps:
[0015] The metal material is immersed in the treatment liquid to form an oxide film on the surface of the metal material.
[0016] 9. The use according to item 7 or 8, wherein the soaking treatment time is 1 to 5 hours, preferably 2 to 3 hours.
[0017] 10. The use according to any one of items 7 to 9, wherein the volume fraction of nitric acid in the treatment liquid is 8% to 12%, and the volume fraction of water is 88% to 92%.
[0018] 11. The use according to any one of items 7 to 10, wherein the treatment liquid consists of nitric acid and water.
[0019] 12. The use according to any one of items 8 to 11, wherein after the oxide film is formed on the surface of the metal material, the surface treatment of the metal material further comprises the steps of cleaning and drying the metal material.
[0020] 13. The use according to any one of items 7 to 12, wherein the metal material is nickel-titanium alloy and / or stainless steel.
[0021] Effects of the Invention
[0022] The present application utilizes a treatment solution containing a certain volume fraction of nitric acid and water to immerse the surface of a metal material so that an oxide film is formed on the surface of the metal material. This can not only effectively improve the damage to the oxide layer on the metal surface caused by external forces, but also maximize the breakdown voltage of the metal material, further improve the corrosion resistance of the metal material, and extend the service life of the metal material. When the metal material has difficult-to-treat parts such as metal connection gaps and welding, the difficult-to-treat parts can be treated to avoid the existence of untreated parts that lead to incomplete oxide film on the surface of the metal material, thereby affecting the corrosion resistance treatment effect of the metal material surface. DETAILED DESCRIPTION
[0023] The present application is further described below in conjunction with the examples, it should be understood that the examples are only used to further illustrate and explain the present application, and are not used to limit the present application. Unless otherwise defined, the technical and scientific terms in this specification are the same as those commonly understood by those skilled in the art. Although similar or identical methods and materials as described herein can be applied in experiments or practical applications, materials and methods are described herein below. In the event of a conflict, this specification including the definitions therein shall prevail, and in addition, materials, methods and examples are for illustration only and are not restrictive.
[0024] In one aspect, the present application provides a method for surface treatment of a metal material, wherein the method comprises the following steps:
[0025] The metal material is immersed in the treatment liquid to form an oxide film on the surface of the metal material;
[0026] The treatment liquid comprises nitric acid and water. In the treatment liquid, the volume fraction of nitric acid is 5% to 15%, and the volume fraction of water is 85% to 95%.
[0027] In a specific embodiment, the volume fraction of nitric acid in the treatment solution is 5-15%, for example, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, etc., preferably 8% to 1 2%; the volume fraction of water is 85% to 95%, for example, it can be 85%, 85.5%, 86%, 86.5%, 87%, 87.5%, 88%, 88.5%, 89%, 89.5%, 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, etc., preferably 88% to 92%.
[0028] In a specific embodiment, the preparation of the treatment solution includes the following steps: adding nitric acid to water, stirring evenly with a glass rod while adding, to obtain a treatment solution in which the volume fraction of the nitric acid is 5% to 15% and the volume fraction of water is 85% to 95%. The nitric acid used to prepare the treatment solution can be commercially available concentrated nitric acid or nitric acid of any volume fraction. This application does not limit the nitric acid used to prepare the treatment solution, but it is necessary to ensure that the final volume fraction of the nitric acid is 5% to 15%, and the final volume fraction of the water is 85% to 95%. In a specific embodiment, the immersion treatment time is 1 to 5 hours, for example, it can be 1h, 1.3h, 1.5h, 1.8h, 2h, 2.3h, 2.5h, 2.8h, 3h, 3.3h, 3.5h, 3.8h, 4h, 4.3h, 4.5h, 4.8h, 5h, etc., preferably 2 to 3h. When the immersion treatment time is less than 2h, the thickness of the oxide film formed on the surface of the metal material is thin, and the corresponding corrosion resistance is relatively poor; when the immersion treatment time is higher than 3h, it will affect the size of the metal material.
[0029] In a specific embodiment, the treatment solution consists of nitric acid and water.
[0030] In a specific embodiment, the treatment solution consists of nitric acid and water, and the soaking treatment time is 1 to 5 hours.
[0031] In a specific embodiment, the metal material surface treatment method of the present application includes the following steps: mixing concentrated nitric acid with a volume fraction of 69% with water to obtain a treatment solution with a volume fraction of 5% to 15% nitric acid and a volume fraction of 85% to 95% water; and immersing the metal material in the treatment solution to form an oxide film on the surface of the metal material.
[0032] In a specific embodiment, after the oxide film is formed on the surface of the metal material, the method further comprises the steps of cleaning and drying the metal material.
[0033] In a specific embodiment, after an oxide film is formed on the surface of a metal material, a treatment liquid remains on the surface of the metal material, and the step of cleaning the metal material includes: placing the metal material in an alkaline solution for cleaning to neutralize the treatment liquid remaining on the surface of the metal material. The present application does not limit the alkaline solution, as long as it can neutralize the treatment liquid remaining on the surface of the metal material and does not damage the oxide film formed by the immersion treatment.
[0034] In a specific embodiment, the step of cleaning the metal material includes: flushing the treatment liquid remaining on the surface of the metal material, ultrasonically cleaning the metal material, flushing the treatment liquid remaining on the surface of the metal material again, placing the metal material in an alkaline solution for cleaning to neutralize the treatment liquid remaining on the surface of the metal material, forming a neutralized product on the surface of the metal material, and cleaning the neutralized product and the residual alkaline solution.
[0035] In a specific embodiment, the metal material is nickel-titanium alloy and / or stainless steel.
[0036] In a specific embodiment, the metal material is nickel-titanium alloy and / or stainless steel, and the surface treatment of the nickel-titanium alloy and / or stainless steel includes the following steps: mixing concentrated nitric acid with a volume fraction of 69% with water to obtain a treatment solution with a volume fraction of 5% to 15% nitric acid and a volume fraction of 85% to 95% water; immersing the nickel-titanium alloy and / or stainless steel in the treatment solution to form an oxide film on the surface of the nickel-titanium alloy and / or stainless steel; cleaning the immersed nickel-titanium alloy and / or stainless steel with an alkaline solution, and then drying to obtain a surface-treated nickel-titanium alloy and / or stainless steel.
[0037] The present application also provides a use of a treatment liquid containing nitric acid and water in the surface treatment of metal materials, wherein the volume fraction of nitric acid in the treatment liquid is 5% to 15%, and the volume fraction of water is 85% to 95%.
[0038] In a specific embodiment, the volume fraction of nitric acid in the treatment solution is 5-15%, for example, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, etc., preferably 8% to 1 2%; the volume fraction of water is 85% to 95%, for example, it can be 85%, 85.5%, 86%, 86.5%, 87%, 87.5%, 88%, 88.5%, 89%, 89.5%, 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, etc., preferably 88% to 92%.
[0039] In one embodiment, the surface treatment of the metal material comprises the following steps:
[0040] The metal material is immersed in the treatment liquid to form an oxide film on the surface of the metal material.
[0041] In a specific embodiment, the immersion treatment time is 1 to 5 hours, for example, it can be 1h, 1.3h, 1.5h, 1.8h, 2h, 2.3h, 2.5h, 2.8h, 3h, 3.3h, 3.5h, 3.8h, 4h, 4.3h, 4.5h, 4.8h, 5h, etc., preferably 2 to 3 hours.
[0042] In a specific embodiment, the treatment solution consists of nitric acid and water.
[0043] In a specific embodiment, the treatment solution consists of nitric acid and water, and the soaking treatment time is 1 to 5 hours.
[0044] In a specific embodiment, the surface treatment of the metal material includes the following steps: mixing concentrated nitric acid with a volume fraction of 69% with water to obtain a treatment solution with a volume fraction of 5% to 15% nitric acid and a volume fraction of 85% to 95% water; and immersing the metal material in the treatment solution to form an oxide film on the surface of the metal material.
[0045] In a specific embodiment, after the oxide film is formed on the surface of the metal material, the method further comprises the steps of cleaning and drying the metal material.
[0046] In a specific embodiment, after an oxide film is formed on the surface of a metal material, a treatment liquid remains on the surface of the metal material, and the step of cleaning the metal material includes: placing the metal material in an alkaline solution for cleaning to neutralize the treatment liquid remaining on the surface of the treated metal material. The present application does not limit the alkaline solution, as long as it can neutralize the treatment liquid remaining on the surface of the metal material and does not damage the oxide film formed by the immersion treatment.
[0047] In a specific embodiment, the step of cleaning the metal material includes: flushing the treatment liquid remaining on the surface of the metal material, ultrasonically cleaning the metal material, flushing the treatment liquid remaining on the surface of the metal material again, placing the metal material in an alkaline solution for cleaning to neutralize the treatment liquid remaining on the surface of the metal material, forming a neutralized product on the surface of the metal material, and cleaning the neutralized product and the residual alkaline solution.
[0048] In a specific embodiment, the metal material is nickel-titanium alloy and / or stainless steel.
[0049] In a specific embodiment, the metal material is nickel-titanium alloy and / or stainless steel, and the surface treatment of the nickel-titanium alloy and / or stainless steel includes the following steps: mixing concentrated nitric acid with a volume fraction of 69% with water to obtain a treatment solution with a volume fraction of 5% to 15% nitric acid and a volume fraction of 85% to 95% water; immersing the nickel-titanium alloy and / or stainless steel in the treatment solution to form an oxide film on the surface of the nickel-titanium alloy and / or stainless steel; cleaning the immersed nickel-titanium alloy and / or stainless steel with an alkaline solution, and then drying to obtain a surface-treated nickel-titanium alloy and / or stainless steel.
[0050] The present application uses a treatment solution containing nitric acid and water to soak the surface of the metal material, so that an oxide film is formed on the surface of the metal material to achieve the purpose of corrosion resistance treatment on the surface of the metal material. This method effectively avoids the damage of the oxide layer on the metal surface by external forces, and at the same time maximizes the breakdown voltage of the metal material, so that the breakdown voltage of the metal material is above 430mV, and can even reach 800mV, significantly improving the corrosion resistance of the metal material and extending the service life of the metal material.
[0051] Example
[0052] The following is a detailed description of the implementation methods of the present application through specific examples, but the following content should not be construed as limiting the present application in any way. The substances used in the examples are all commercially available products unless otherwise specified.
[0053] Example 1
[0054] 1.1 Configuration of treatment fluid
[0055] Add nitric acid into water and stir evenly with a glass rod to prepare a treatment solution with a nitric acid volume fraction of 8%.
[0056] 1.2 Processing of metal samples
[0057] A nickel-titanium alloy sample with a thickness of 0.500±0.025 (mm) to be treated (nickel mass percentage of 54.5-57.0%, titanium mass percentage balance, carbon mass percentage ≤5%, cobalt mass percentage ≤5%, copper mass percentage ≤1%, chromium mass percentage ≤1%, hydrogen mass percentage ≤0.5%, iron mass percentage ≤5%, niobium mass percentage ≤2.5%, nitrogen and oxygen mass percentages ≤5%, Euroflex) is added to the treatment solution for immersion treatment and allowed to stand at room temperature for 2 hours. During this process, the treatment solution reacts with the metal surface to form an oxide film. After the treatment is completed, the sample is taken out with tweezers.
[0058] 1.3 Washing of treatment solution
[0059] 1) First, place the treated nickel-titanium alloy sample in running water and shake it to clean it, so as to preliminarily rinse the treatment solution on the surface of the nickel-titanium alloy;
[0060] 2) Place the sample in a beaker filled with purified water and perform ultrasonic cleaning at room temperature for 1 min (ultrasonic power of 250 W, frequency of 53 KHz, Kedao SK250HP) to rinse the surface of the nickel-titanium alloy sample with the treatment solution again;
[0061] 3) The nickel-titanium alloy sample was then placed in a 10 wt % sodium carbonate solution for ultrasonic cleaning for 1 min (ultrasonic power of 250 W, frequency of 53 KHz, Kedao SK250HP) to neutralize the treatment solution remaining on the surface of the nickel-titanium alloy sample;
[0062] 4) placing the nickel-titanium alloy sample cleaned in a 10 wt % sodium carbonate solution in running water and shaking to clean it, thereby preliminarily rinsing the neutralized product and the sodium carbonate solution on the surface of the nickel-titanium alloy sample;
[0063] 5) Then put it into purified water for ultrasonic cleaning for 1 minute with an ultrasonic power of 250W and a frequency of 53KHz (SK250HP), and rinse the neutralized product and sodium carbonate solution on the surface of the nickel-titanium alloy sample again;
[0064] 6) Finally, wash in anhydrous ethanol for 1 min, then dry in a 60°C oven for 10 min, and take out after drying.
[0065] Example 2
[0066] The only difference between this embodiment and embodiment 1 is that the volume fraction of nitric acid in the treatment solution is 5%.
[0067] Example 3
[0068] The only difference between this embodiment and embodiment 1 is that the volume fraction of nitric acid in the treatment solution is 12%.
[0069] Example 4
[0070] The only difference between this embodiment and embodiment 1 is that the volume fraction of nitric acid in the treatment solution is 10%.
[0071] Example 5
[0072] The only difference between this embodiment and embodiment 1 is that the volume fraction of nitric acid in the treatment solution is 15%.
[0073] Example 6
[0074] The only difference between this embodiment and embodiment 1 is that the metal material sample used is stainless steel (316L stainless steel in accordance with GB234.1).
[0075] Example 7
[0076] The only difference between this embodiment and embodiment 1 is that the nickel-titanium alloy sample is immersed in the treatment solution for 5 hours.
[0077] Example 8
[0078] The only difference between this embodiment and embodiment 1 is that the nickel-titanium alloy sample is immersed in the treatment solution for 1 hour.
[0079] Example 9
[0080] The only difference between this embodiment and embodiment 1 is that the nickel-titanium alloy sample is immersed in the treatment solution for 3 hours.
[0081] Example 10
[0082] The only difference between this embodiment and embodiment 1 is that the nickel-titanium alloy sample is immersed in the treatment solution for 4 hours.
[0083] Comparative Example 1
[0084] The only difference between this comparative example and Example 1 is that the volume fraction of nitric acid in the treatment solution is 2%.
[0085] Comparative Example 2
[0086] The only difference between this comparative example and Example 1 is that the volume fraction of nitric acid in the treatment solution is 20%.
[0087] Comparative Example 3
[0088] The only difference between this comparative example and Example 1 is that the treatment liquid is nitric acid with a volume fraction of 69%.
[0089] Comparative Example 4
[0090] The only difference between this comparative example and Example 1 is that the treatment liquid is a sulfuric acid aqueous solution, and the volume fraction of sulfuric acid in the treatment liquid is 8%.
[0091] Comparative Example 5
[0092] The only difference between this comparative example and Example 1 is that the treatment liquid is a hydrofluoric acid aqueous solution, and the volume fraction of hydrofluoric acid in the treatment liquid is 8%.
[0093] Comparative Example 6
[0094] The only difference between this comparative example and Example 1 is that the treatment liquid consists of nitric acid, hydrofluoric acid and water, the volume fraction of nitric acid in the treatment liquid is 20%, and the volume fraction of hydrofluoric acid is 10%.
[0095] Comparative Example 7
[0096] The only difference between this comparative example and Example 1 is that the nickel-titanium alloy sample is not subjected to surface treatment.
[0097] The treatment liquid compositions, metal material sample types, treatment conditions, and properties of the treated samples of the embodiments and comparative examples are listed in Table 1 below.
[0098] Table 1
[0099]
[0100]
[0101] As can be seen from Table 1 above, the breakdown voltage of the metal material with an oxide film on the surface obtained by immersing the metal material in a treatment solution mixed with concentrated nitric acid and water using the surface treatment method of the present application is greater than 430mV. After immersion treatment for 2h using a treatment solution with a volume fraction of 10% nitric acid, the breakdown voltage of the nickel-titanium alloy can reach 800mV, and when the nickel-titanium alloy and stainless steel are treated with the same 8% nitric acid treatment solution, the breakdown voltage of the treated nickel-titanium alloy is significantly higher than that of the treated stainless steel. The breakdown voltage of the metal material treated with a treatment solution with a volume fraction of nitric acid exceeding 15% or less than 5% is lower than the breakdown voltage of the metal material treated with the treatment solution of the present application. The above experimental results fully illustrate that the oxide film formed on the metal surface by the surface treatment method of the present application can improve the breakdown voltage of the metal material, improve the corrosion resistance of the metal material, and extend the service life of the metal material.
[0102] The above is only the preferred embodiment of the present application, and does not limit the present application in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present application without departing from the technical solution of the present application still falls within the protection scope of the technical solution of the present application.
Claims
1. A method for surface treatment of a metal material, wherein: The method comprises the following steps: The metal material is immersed in the treatment liquid to form an oxide film on the surface of the metal material; The treatment liquid comprises nitric acid and water. In the treatment liquid, the volume fraction of nitric acid is 5% to 15%, and the volume fraction of water is 85% to 95%.
2. The method according to claim 1, wherein: The soaking treatment time is 1 to 5 hours, preferably 2 to 3 hours.
3. The method according to claim 1, wherein: In the treatment liquid, the volume fraction of nitric acid is 8% to 12%, and the volume fraction of water is 88% to 92%.
4. The method according to any one of claims 1 to 3, wherein: The treatment liquid consists of nitric acid and water.
5. The method according to any one of claims 1 to 4, wherein: After the oxide film is formed on the surface of the metal material, the method further comprises the steps of cleaning and drying the metal material.
6. The method according to any one of claims 1 to 5, wherein: The metal material is nickel-titanium alloy and / or stainless steel.
7. Use of a treatment solution containing nitric acid and water in the surface treatment of metal materials, wherein: In the treatment liquid, the volume fraction of nitric acid is 5% to 15%, and the volume fraction of water is 85% to 95%.
8. The use according to claim 7, wherein The surface treatment of metal materials includes the following steps: The metal material is immersed in the treatment liquid to form an oxide film on the surface of the metal material.
9. The use according to claim 7 or 8, wherein The soaking treatment time is 1 to 5 hours, preferably 2 to 3 hours.
10. The use according to any one of claims 7 to 9, wherein In the treatment liquid, the volume fraction of nitric acid is 8% to 12%, and the volume fraction of water is 88% to 92%.
11. The use according to any one of claims 7 to 10, wherein The treatment liquid consists of nitric acid and water.
12. The use according to any one of claims 8 to 11, wherein After an oxide film is formed on the surface of the metal material, the surface treatment of the metal material further includes the steps of cleaning and drying the metal material.
13. The use according to any one of claims 7 to 12, wherein The metal material is nickel-titanium alloy and / or stainless steel.
